Investigation of the effects of Nepeta italica subsp. cadmea extract on frozenthawed Ankara buck spermatozoa - Boztaş, S; Keskin, N; Bucak, MN; Er Urgancı, B; Bodu, M; Taspinar, F (Journal of the Hellenic Veterinary Medical Society, 2025)
Semen cryopreservation causes adverse effects on the sperm structure especially on plasmalemma, acrosomes and DNA which results in lowered fertilization capacity. Hereby, cryoprotective antioxidant molecules have been extensively investigated to overcome the deleterious effects of oxidative stress caused by cryopreservation in spermatozoa. In recent years, natural antioxidants rich in flavonoids and phenolic compounds have gained increasing attention to develop as novel cryoprotectants in spermatozoa cryopreservation. Nepeta italica subsp. cadmea (Boiss.) rich in terpenoids and flavonoids is endemic to Turkey. In this study, the effects of three different doses of Nepeta italica subsp. cadmea essential oil (0.75 µL/10 mL, 1.5 µL/10 mL and 6 µL/10 mL) on motility, acrosome integrity, mitochondrial activity and DNA fragmentation in frozen-thawed Ankara buck spermatozoa were investigated. The plants were harvested during the flowering stage on Honaz Mountain (Denizli, Turkey) and air dried in the shade at room temperature. The essential oil of the powdered plant was extracted by hydrodistillation using a Clevenger apparatus system, then stored at 4 °C in an amber colored glass bottle. The ejaculates taken from the Ankara bucks during the breeding season with an electroejaculator were combined and used in the diluting and freezing of semen. The extender groups were formed by adding three different doses of Nepeta italica subsp. cadmea essential oil (0.75 µL/10 mL, 1.5 µL/10 mL and 6 µL/10 mL) to the control extender. The semen was diluted with the different extenders at 35–37 °C and loaded into straws. Sperm samples frozen in liquid nitrogen vapors, following equilibration, were stored in liquid nitrogen. The plant essential oil at the dose of 0.75 µL/10 mL improved motility, acrosome integrity, mitochondrial activity and DNA fragmentation in post-thawed Ankara buck spermatozoa (p<0.05). As a result, it can be suggested that the most effective dose of 0.75 µL/10 mL of Nepeta italica subsp. cadmea (Boiss.) essential oil can be used as an effective additive for freezing Ankara buck spermatozoa.